The Untia Coastal Tourism Village: The Driving Force Behind the Development of Makassar's New Port - Rahayu, Mia; Eppang, Buntu Marannu; Renold; Machmury, Andri; Muchlis, Farah Fajriaty; Ridwan, Masri; Pastini, Ni Wayan; Oktawirani, Panca (International Journal of Qualitative Research, 2024)
The development of the sea highway through the Makassar New Port project is a threat to the management of the Untia Fishermen's Village tourism area, Makassar City. So far, the potential of mangroves in Untia Fishermen Village has become a tourist attraction. The resilience of coastal communities is needed to deal with changes in the coastline caused by Makassar New Port. This research aims to discover the socio-cultural potential in the Untia Fishermen Village so that it can be developed into a creative economic business to adapt to changes in the environment around the area. The research was conducted qualitatively by interviewing and observing four informants who have played a role in the governance of Untia Fishermen Village. Data analysis was performed using SWOT. The results showed that the strengths in the study location are social capital in the form of creativity, compliance with rules, and awareness of managing plastic waste. In comparison, the existing obstacle is the inability to use digital marketing, which still needs to be improved. Collaboration of all parties is required through community empowerment activities and establishing strategic government programs for fishing communities threatened with losing their livelihoods as fishermen.